NUMERICAL STUDY OF THE PRESSURE CORRECTION PROCESS FOR FLOW OF IMMIXIBLE INCOMPRESSIBLE FLUIDS - Shiyapov К.; Baishemirov Ж; Zhanbyrbayev А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
Scientific research in the field of numerical modeling and analysis of the relationship between the velocity vector and pressure in immiscible incompressible fluids is relevant and important in various engineering and physical applications. This issue is directly related to many engineering problems, such as the development and optimization of fluid transport systems, hydrodynamic systems and their automation. Understanding the relationship between velocity and pressure in immiscible fluids can help evaluate the effects of various factors. This paper considers a numerical study of the relationship between the velocity vector and pressure for flows of immiscible incompressible fluids, which takes into account calculations of the velocity field at each time using a pressure correction procedure consisting of two stages. As a result, the pressure increase mode is carried out due to the separation of released liquid droplets from the free boundary and their further distribution along the capillary.